Nanoparticle-Encapsulated Curcumin Inhibits Diabetic Neuropathic Pain Involving the P2Y12 Receptor in the Dorsal Root Ganglia - Jia, Tianyu; Rao, Jingan; Zou, Lifang; Zhao, Shanhong; Yi, Zhihua; Wu, Bing; Li, Lin; Yuan, Huilong; Shi, Liran; Zhang, Chunping; Gao, Yun; Liu, Shuangmei; et al. (Frontiers in Neuroscience, 2018)
Diabetic peripheral neuropathy results in diabetic neuropathic pain (DNP). Satellite glial cells (SGCs) enwrap the neuronal soma in the dorsal root ganglia (DRG). The purinergic 2 (P2) Y12 receptor is expressed on SGCs in the DRG. SGC activation plays an important role in the pathogenesis of DNP. Curcumin has anti-inflammatory and antioxidant properties. Because curcumin has poor metabolic stability in vivo and low bioavailability, nanoparticle-encapsulated curcumin was used to improve its targeting and bioavailability. In the present study, our aim was to investigate the effects of nanoparticle-encapsulated curcumin on DNP mediated by the P2Y12 receptor on SGCs in the rat DRG. Diabetic peripheral neuropathy increased the expression levels of the P2Y12 receptor on SGCs in the DRG and enhanced mechanical and thermal hyperalgesia in rats with diabetes mellitus (DM). Up-regulation of the P2Y12 receptor in SGCs in the DRG increased the production of pro-inflammatory cytokines. Up-regulation of interleukin-1β (IL-1β) and connexin43 (Cx43) resulted in mechanical and thermal hyperalgesia in rats with DM. The nanoparticle-encapsulated curcumin decreased up-regulated IL-1β and Cx43 expression and reduced levels of phosphorylated-Akt (p-Akt) in the DRG of rats with DM. The up-regulation of P2Y12 on SGCs and the up-regulation of the IL-1β and Cx43 in the DRG indicated the activation of SGCs in the DRG. The nano-curcumin treatment inhibited the activation of SGCs accompanied by its anti-inflammatory effect to decrease the up-regulated CGRP expression in the DRG neurons. Therefore, the nanoparticle-encapsulated curcumin treatment decreased the up-regulation of the P2Y12 receptor on SGCs in the DRG and decreased mechanical and thermal hyperalgesia in rats with DM.